Clinical case studies in home health care - Neal-Boylan, Leslie (Wiley-Blackwell, 2011)
Home health care is an important aspect of community health and a growing area of healthcare services. Clinical Case Studies in Home Health Care uses a case-based approach to provide home health care professionals, educators, and students with a useful tool for thoughtful, holistic care. The book begins with a thorough and accessible introduction to the principles of home health care, including a discussion of supporting theoretical frameworks and information on managing complexities, transitioning patients to home care, and preparation for the home visit. Subsequent sections are comprised ent.